ANALYSIS OF OPEN GOVERNMENT: A REVIEW OF FOOD SECURITY AND INDEPENDENCE POLICY IN BOJONEGORO - Septiana, Vita Nugrah; Kumalasari*, Ana; Junadi, Junadi; Musa, Hussein Gibreel (JWP (Jurnal Wacana Politik), 2025)
This study examines how Open Government initiatives enhance the effectiveness of the Independent Farmer Card (KPM) Plus Program and their subsequent impacts on Food Security and Food Independence among rural communities. The research problem of this study is that some farmers lack an understanding of how to access support and follow application instructions for agricultural aid through the KPM Plus Program. The research analyzes the impact of transparency, participation, and collaboration within government frameworks on agricultural support. The findings highlight that Open Government initiatives significantly enhance the effectiveness of the KPM Plus Program, leading to better food security and independence for farmers. While SEM results confirm that strong governance positively influences agricultural programs, the model’s fit indices indicate a need for refinement to capture the underlying dynamics better. The study recommends strengthening Open Government practices to enhance program effectiveness and food security in rural areas. Future research should consider additional variables and refine the model for deeper insights into the relationship between governance and agriculture. This research contributes valuable perspectives on rural development, highlighting the importance of transparent and participative governance in advancing agricultural support and food sustainability.